2012
DOI: 10.1186/1471-2482-12-s1-s18
|View full text |Cite
|
Sign up to set email alerts
|

Ankle/brachial index to everyone

Abstract: BackgroundIn the last years significant attention has been paid in identifying markers of subclinical atherosclerosis or of increased cardiovascular risk.MethodAn abnormal ankle/brachial index (ABI) identifies patients affected by lower extremity peripheral arterial disease, and even more important, represents a powerful predictor of the development of future ischemic cardiovascular events.ConclusionsIn our opinion, ABI is a cardiovascular risk prediction tool with very desirable properties that might become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Patients with prehypertension have increased carotid intima-media thickness, greater left ventricle hypertrophy and more development of diastolic dysfunction when compared with normotensive subjects,12, 13 those patients also have greater incidence of myocardial infarction, stroke and cardiovascular death 11 . Since a low ABI predicts high cardiovascular risk, our results supports the evidence that prehypertensive patients are a high cardiovascular risk group.…”
Section: Discusionsupporting
confidence: 80%
See 1 more Smart Citation
“…Patients with prehypertension have increased carotid intima-media thickness, greater left ventricle hypertrophy and more development of diastolic dysfunction when compared with normotensive subjects,12, 13 those patients also have greater incidence of myocardial infarction, stroke and cardiovascular death 11 . Since a low ABI predicts high cardiovascular risk, our results supports the evidence that prehypertensive patients are a high cardiovascular risk group.…”
Section: Discusionsupporting
confidence: 80%
“…A low ABI is an independent predictor of future cardiovascular events, and the risk increases with the reduction of ABI values even in absence of other cardiovascular risk factors, and in patients without PAD; then, the ABI measurement provides additional information for the stratification of cardiovascular risk. A low ABI leads to a high cardiovascular risk with a different therapeutic approach 8, 11…”
Section: Discusionmentioning
confidence: 99%
“…1 Similar to previous reports, [2][3][4] this study concluded that the ABI can be used for PAD screening as well as to monitor the treatment of PAD. This editorial considers the pros and cons of screening for PAD.…”
supporting
confidence: 69%
“…The symptoms and prognosis of patients with PAD vary according to the location and size of the affected arteries. 31 Some support routine screening for PAD for all, 4 but others maintain that the evidence is insufficient to recommend such screening. 25 Although it is probably true that general population screening for PAD is not cost effective, specific patient subgroups (eg, those with DM, smokers, or the elderly without known CVD) may benefit from ABI measurement in the primary care setting.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 ] PAD, the silent killer in T2DM denies classical claudication[ 4 ] and in countries like ours can culminate into diabetic foot threatening limbs. This requires assessment in preclinical stage by simple yet under-used tool like ankle-brachial index (ABI)[ 5 ] which was utilized in our study. In previous articles, we have published high prevalence of PAD,[ 6 ] effect of risk factors,[ 3 ] importance of good glycemic control,[ 7 ] and benefit from angiotensin II converting enzyme inhibitors[ 8 ] in our T2DM subjects.…”
Section: Introductionmentioning
confidence: 99%